Pengaruh Penerapan Kebijakan Sistem Manajemen Keselamatan Dan Kesehatan (SMK3) Terhadap Kepuasan Kerja Tenaga Kerja Pada Proyek Kantor Perwakilan Bank Indonesia Provinsi Bali - I Ketut Sutapa; I Nyoman Suardika; Made Sudiarsa; I Kadek Andita Putra (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2021)
This study aims to determine how much effect the implementation of SMK3 policies on workforce satisfaction in construction projects. In this study using descriptive quantitative research methods. The data collection method used a questionnaire that was distributed to the project workforce using 25 people as a sample. The research instrument test used the validity test, reliability test, multicollinearity test, and probability plot normality test, while the data analysis method used multiple linear regression analysis, F test and t test. The research results can be concluded as follows. First, the SMK3 policy variable that has the most dominant influence on workforce job satisfaction is the variable of implementing the K3 plan. Second, the SMK3 policy variables, namely, the establishment of OHS policies, OHS planning, implementation of K3 plans, monitoring and evaluation of K3 performance, and reviewing and improving SMK3 performance have a joint effect on job satisfaction of workers in the project.